EVALUASI PEMASANGAN APAR DALAM SISTEM TANGGAP DARURAT KEBAKARAN DI GEDUNG BEDAH RSUD DR. SOETOMO SURABAYA - Rizki Fitriana Hambyah (The Indonesian Journal of Occupational Safety and Health, 2016)
Fire extinguisher is one of the active fire protection system that is used to extinguish fires are still small and used in emergencies, so as to prevent that no larger fires that cause harm and even fatalities. The aim of this study was to evaluate the installation of fire extinguisher in a fire emergency response system in the building surgical at Dr. Soetomo Hospital. This type of this study is evaluative research. Data were collected through observation, and measurement. Variables studied, namely the installation of fire extinguisher. Technique of analysis in this study is to use comparative approach to determine the suitability of the installation of a fire extinguisher that compared with Permenakertrans No. PER.04/MEN/1980. The approach taken were to semi quantitative to see how large the proportion of the suitability of the installation of a fire extinguisher in the surgical building at Dr. Soetomo Hospital. The results showed that at the Dr. Soetomo Hospital have fire emergency response system and has been applied. Installation fire extinguishers in the surgical building at Dr. Soetomo Hospital generally not meet the requirements of Permenakertrans No. PER.04/MEN/1980. There still is a fire extinguisher in the surgical building kind of halon in Bogenvil, Cempaka, Gladiol, Herbra and Nusa Indah. There is a fire extinguisher expired, in the surgical building at Cempaka, Dahlia, Flamboyan and Hebra.Keywords: portable fire extinguisher, surgical building, Dr. Soetomo hospital